A study of treatment outcomes of pulmonary tuberculosis and extrapulmonary tuberculosis patients in a tertiary care centre - Ramya, V. H.; Gayathri, G.; Gangadharan, V. (International Journal of Advances in Medicine, 2017)
Background: Directly observed treatment remains one of the most widely-accepted global health interventions for tuberculosis. Tuberculosis treatment outcome is one of the performance indicators of the programme set by World Health Organization. Methods: This study was conducted in a tertiary care centre Chennai. A retrospective analysis of the profile and treatment outcome of all tuberculosis patients registered from January 2015 to December 2015 at DOTS centre under RNTCP was conducted. Data on treatment outcomes was analysed using appropriate statistical methods and percentages were calculated. Results: Out of 118 TB cases, 59.3% had pulmonary while 40.7% had extra-pulmonary TB. Sputum positive PTB is more common than sputum negative which is 74.2% and 25.8% respectively. Frequency of TB lymphadenitis is being the common presentation among extra pulmonary TB cases, followed by TB pleurisy. Success rate (cure rate plus treatment completion rate) for new cases was 63.1% and for retreatment cases was 36.9% while the overall success rate was 81%. Conclusions: Effective measures have to be taken in the programme to move forward to help in the eradication of TB. Tuberculosis mostly affects males of the economically productive age group and causes economic losses. The success rate of new cases was higher compared to retreatment cases though the overall success rate was lower compared to the RNTCP norms. Proper education on DOTS can help in improving the success rate and cure rate.